Review Of Vo2max Volleyball Athletes Club Rekita Vc Dikoto Gasib Kabupaten Siak - Mariana Tiurmaida; Oki Candra (CV. AFDIFAL MAJU BERKAH, 2024)
The aim of this research was to examine the VO2 Max abilities of Rekita VC Club volleyball athletes in Koto Gasib, Kabupaten Siak. Based on the results of observations made on Rekita VC Club volleyball athletes in Koto Gasib, Kabupaten Siak, it was found that several problems arose, on average the athletes had unstable endurance when playing volleyball. This situation is influenced by a lack of time for physical training and a lack of seriousness when doing physical training and being too focused on having fun matches or sparring partners between clubs. Seeing the progress during their training, some athletes have unstable endurance and are less diligent in carrying out physical training so that the athlete's physical condition is still not perfect. The test used in this research was the bleep test to see VO2 Max abilities . The sample in this study was 11 people. From the results of tests carried out on Rekita VC Club volleyball athletes in Koto Gasib, Kabupaten Siak, results were obtained in the